Rearrangements of dicarba-nido-undecaborates - S. P. Knyazev; A. Yu. Kostiykovitch (Тонкие химические технологии)
The thermal and chemically initiated thermal rearrangements of dicarba-nido-undecaborates was explored by computational chemistry. It was shown that the kinetic stability of dianions of these compounds is reduced in the series 2,9 > 7,8 > 1,7 > 2,4 > 2,8 > 1,2 >2,7 > 2,3.